Struktur Pertunjukan dan Interaksi Simbolik Barongan Kusumojoyo di Demak - Prasena Arisyanto; Mei Fita Asri Untari; Riris Setyo Sundari (Gondang: Jurnal Seni dan Budaya, 2019)
Barongan is one of traditional arts owned by society in Demak regency. Barongan born and developed together with its supporting community, one of them is Barongan Kusumojoyo’s group. This research aims to analyze the structure and symbolic interaction of Barongan Kusumojoyo performing arts. Research methods use qualitative with ethnographic design. Data collection use observation, interview, and document study. Data analysis use theory of form of the show, structural functional, and symbolic interaction, with three steps of analysis. Data validation use technical triangulation and source triangulation. Research result conclude that structure of Barongan Kusumojoyo performing arts often change for each perform. The difference is caused by the purpose of each different performing. Performing structure for entertainment and performing structure for aesthetic or art festival are different. Main difference is seen by story in every perform, especially in aesthetic perform. Symbolic interaction in Barongan Kusumojoyo performing art can be observed from ornament of the show like ornament in mask, property, costume, and sesajen. Ornaments that appear are cultural ornament and decorative ornament. The most important is audience and sponsor feel happy and satisfied with Barongan Kusumojoyo performing arts.